2013
DOI: 10.3390/e15083339
|View full text |Cite
|
Sign up to set email alerts
|

Truncation Effects of Shift Function Methods in Bulk Water Systems

Abstract: A reduction of the cost for long-range interaction calculation is essential for large-scale molecular systems that contain a lot of point charges. Cutoff methods are often used to reduce the cost of long-range interaction calculations. Molecular dynamics (MD) simulations can be accelerated by using cutoff methods; however, simple truncation or approximation of long-range interactions often offers serious defects for various systems. For example, thermodynamical properties of polar molecular systems are strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 67 publications
3
11
0
Order By: Relevance
“…To make the IPS technique ubiquitous for homogeneous and heterogeneous systems, we have developed the linear‐combination‐based IPS (LIPS) method, which is an improved IPS method using the linear combination of basis potentials based on an extended IPS theory . The LIPS method successfully extends the range of application of the IPS technique and can accurately estimate both homogeneous and heterogeneous systems of nonpolar and/or polar molecules . The algorithm of the LIPS method for interaction calculations is the same as that of the conventional IPS method, regardless of the extension of the IPS techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To make the IPS technique ubiquitous for homogeneous and heterogeneous systems, we have developed the linear‐combination‐based IPS (LIPS) method, which is an improved IPS method using the linear combination of basis potentials based on an extended IPS theory . The LIPS method successfully extends the range of application of the IPS technique and can accurately estimate both homogeneous and heterogeneous systems of nonpolar and/or polar molecules . The algorithm of the LIPS method for interaction calculations is the same as that of the conventional IPS method, regardless of the extension of the IPS techniques.…”
Section: Introductionmentioning
confidence: 99%
“…[74] The LIPS method successfully extends the range of application of the IPS technique and can accurately estimate both homogeneous and heterogeneous systems of nonpolar and/or polar molecules. [74][75][76] The algorithm of the LIPS method for interaction calculations is the same as that of the conventional IPS method, regardless of the extension of the IPS techniques. Therefore, IPS/ Tree can be easily assimilated with the LIPS method.…”
Section: Introductionmentioning
confidence: 99%
“…An advanced cutoff method was developed by Wolf et al [16]. This pairwise summation approach is much simpler than the Ewald sum [13] but gives similar results [12]. The approach of Wolf et al has been further modified by Fennell and Gezelter [12], and it could be shown that an approximately linear scaling~N can be achieved.…”
Section: Classical Molecular Dynamicsmentioning
confidence: 95%
“…To achieve an acceleration of the calculation, so-called cutoff methods can be applied. Here, the interactions between the particles are only considered for distances shorter than a specified cutoff radius, and the effects from distances larger than the cutoff are truncated or approximated [13]. A discontinuous truncation of the Coulomb potential at the cutoff distance can lead to unacceptable artifacts [14].…”
Section: Classical Molecular Dynamicsmentioning
confidence: 99%
“…This effect was also observed for switch/shift functions and the reaction field method with group-based cut-off 28 , 30 . Importantly, these defects were clearly reduced when using atom-based cut-off 37 . Thus we reason that group-based cut-off is more prone to erroneous behaviour than atom-based cut-off, and careful investigation is required.…”
Section: Introductionmentioning
confidence: 99%